Estrategias Econ.para las Decisiones Empresariales - AF189 - 202302 - Escalante Márquez, Andrés Alejandro (2023)
Description: Economics of strategy allows us to make decisions in a more informed way. Analysis of available choices combined with consequences and outcomes lead the possibilities that can unfold. While these decisions take place in our daily lives, few stop to consider how a different outcome could unfold if several other options were considered. We will apply strategic decision making to a variety of business scenarios to understand the value in a changing organization, when dealing with competition and how to innovate. PREREQUISITE: ECON 220 Basic Economic Issues